Nck2, an unexpected regulator of adipogenesis. (3rd April 2017) - Haider, N.; Dusseault, J.; Rudich, A.; Larose, L.
ABSTRACT: The regulation of adipose tissue expansion by adipocyte hypertrophy and/or hyperplasia is the topic of extensive investigations given the potential differential contribution of the 2 processes to the development of numerous chronic diseases associated with obesity. We recently discovered that the loss-of-function of the Src homology domain-containing protein Nck2 in mice promotes adiposity accompanied with adipocyte hypertrophy and impaired function, and enhanced adipocyte differentiation in vitro . Moreover, in severely-obese human's adipose tissue, we found that Nck2 expression is markedly downregulated. In this commentary, our goal is to expand upon additional findings providing further evidence for a unique Nck2-dependent mechanism regulating adipogenesis. We propose that Nck2 should be further investigated as a regulator of the reliance of white adipose tissue on hyperplasia versus hypertrophy during adipose tissue expansion, and hence, as a potential novel molecular target in obesity.